Effects of Oil and Natural Gas Prices on Industrial Production In the Eurozone Member Countries - BAYAR, Yılmaz; KILIC, Cuneyt (International Journal of Energy Economics and Policy, 2014)
Industrial production is one of the leading indicators of gross domestic product which reflects the overall economic performance of a country. In other words decreases or increases in industrial production point out a contracting or expanding economy. Therefore, changes in prices of oil and natural gas which are the crucial inputs to the industrial production are also important for the overall economy. This study examines the effects of changes in oil and natural gas prices on the industrial production in the 18 Eurozone member countries during the period January 2001-September 2013 by using panel regression. We found that oil prices and natural gas prices had negative effect on industrial production in the Eurozone member countries. Keywords: Oil Prices; Natural Gas Prices; Industrial Production; Eurozone Member Countries; Panel Data Analysis. JEL Classifications: C22; E31; L60; Q43.